Elemental carbon, organic carbon, and dust concentrations in snow measured with thermal optical and gravimetric methods: Variations during the 2007–2013 winters at Sapporo, Japan. Issue 2 (27th January 2015) - Kuchiki, Katsuyuki; Aoki, Teruo; Niwano, Masashi; Matoba, Sumito; Kodama, Yuji; Adachi, Kouji
Abstract The mass concentrations of light‐absorbing snow impurities at Sapporo, Japan, were measured during six winters from 2007 to 2013. Elemental carbon (EC) and organic carbon (OC) concentrations were measured with the thermal optical method, and dust concentration was determined by filter gravimetric measurement. The measurement results using the different filters were compared to assess the filtration efficiency. Adding NH4H2PO4 coagulant to melted snow samples improved the collection efficiency for EC particles by a factor of 1.45. The mass concentrations of EC, OC, and dust in the top 2 cm layer ranged in 0.007–2.8, 0.01–13, and 0.14–260 ppmw, respectively, during the six winters. The mass concentrations and their short‐term variations were larger in the surface than in the subsurface. The snow impurity concentrations varied seasonally; that is, they remained relatively low during the accumulation season and gradually increased during the melting season. Although the surface snow impurities showed no discernible trend over the six winters, they varied from year to year, with a negative correlation between the snow impurity concentrations and the amount of snowfall. The surface snow impurities generally increased with the number of days elapsed since snowfall and showed a different rate for EC (1.44), OC (9.96), and dust (6.81). The possible processes causing an increase in surface snow impurities were dry deposition of atmospheric aerosols, melting of surface snow, and sublimation/evaporation of surface snow.